2014 IEEE International Electron Devices Meeting 2014
DOI: 10.1109/iedm.2014.7047045
|View full text |Cite
|
Sign up to set email alerts
|

A Schottky-barrier silicon FinFET with 6.0 mV/dec Subthreshold Slope over 5 decades of current

Abstract: In this paper, we demonstrate a steep Subthreshold Slope (SS) silicon FinFET with Schottky-barrier source/drain. The device shows a minimal SS of 3.4 mV/dec and an average SS of 6.0 mV/dec over 5 decades of current swing. Ultra-low leakage floor of 0.06 pA/µm is also achieved with high I on /I off ratio of 10 7 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 8 publications
1
59
0
1
Order By: Relevance
“…The symmetrical part 0 f of the BTE is obtained after substituting the explicit forms of the electric field and collision terms into equation (2). The details of the procedure are given in literatures [13,6] for lattice at room temperature.…”
Section: Analytical Formulation Of Btementioning
confidence: 99%
See 1 more Smart Citation
“…The symmetrical part 0 f of the BTE is obtained after substituting the explicit forms of the electric field and collision terms into equation (2). The details of the procedure are given in literatures [13,6] for lattice at room temperature.…”
Section: Analytical Formulation Of Btementioning
confidence: 99%
“…Hot carrier multiplication leads to avalanche breakdown in advanced scale bipolar devices, substrate current leakage in UTBOX FDSOI MOSFET [1] and the performance a Schottky-Barrier Silicon FinFET [2]. Impact ionization (II), which is the central generation process reliable for the breakdown, plays an important role in device degradation failure threshold in electrostatic discharge (ESD) protection and power devices.…”
Section: Introductionmentioning
confidence: 99%
“…Reference [9] showed that for a 50-μm-thick silicon fabric, the fracture stress is about 1.1 GPa. Substituting a (100) silicon Young's modulus of 128 GPa [10] in Equation (1), and the resulting strain value from Equation (2), we obtain a minimum bending radius for the 50-μm-thick flexible silicon fabric of approximately 3 mm, which decreases with a decreasing thickness. Therefore, a plain flexible silicon substrate that is 50-μm-thick or thinner with a bending radius of more than 3 mm will safely operate below the fracture stress level.…”
Section: A Silicon's Bending Ability and Limitationsmentioning
confidence: 99%
“…They must have low power consumption (dynamic and static), high performance, and flexibility. Subthreshold swing (SS) is a critical parameter to this end because it affects the switching speed of a transistor and its dynamic power consumption [1].…”
Section: Introductionmentioning
confidence: 99%
“…Such transistors with CP have been successfully implemented in SiNWs [9], [10], carbon nanotube [26], graphene [27], and FinFET [28]. In such transistors, one electrode gate, the control gate (CG), works like conventional MOSFETS, and provides the conduction by controlling potential barriers.…”
Section: A Transistors With Cpmentioning
confidence: 99%